The Effect of Kepok Banana Peel Flour Substitution on the Hedonic Test of Malang's Signature Souvenir Product "Banana Strudel" - Krisnanda, Rulli; Sabrina, Arzendy Berlian; Indriani, Dewi; Anam, Mochammad Musafaul (JURNAL GASTRONOMI INDONESIA, 2025)
Abstract This study explores the utilization of kepok banana peel waste as a flour substitute in the production of Banana Strudel, a signature souvenir from Malang City. Kepok banana peels, typically discarded as waste, were processed into flour to enhance their utility and extend their shelf life. The study employed a descriptive experimental approach with four formulations of banana peel flour (15 g, 20 g, 25 g, and 30 g). A hedonic test was conducted to evaluate the taste, color, and texture of the puff pastry resulting from the substitution. The results showed that the 25 g formulation of banana peel flour achieved the highest scores for taste (3.70), color (3.56), and texture (3.43) on the consumer preference scale. However, the impact of flour gram formulation on texture was not significant. This substitution imparted unique taste and color attributes that could enhance the product’s appeal. The study contributes to the development of innovative products based on local wisdom and environmental sustainability. Further recommendations include market analysis and scaling up production for commercialization